Emergency patients’ satisfaction with humanistic caring and its associated factors in Chinese hospitals: a multi-center cross-sectional study - Wang, Wei; Liu, Xinwen; Shen, Xiulan; Zhang, Jichun; Zhang, Fengying; Liao, Lulu; He, Xiaoxiao; Liu, Yilan (Frontiers in Public Health, 2024)
Humanistic caring in clinical practice is important for quality care and patient satisfaction.satisfaction. The application of humanistic care in emergency department has also been reported. This study aimed to assess patient satisfaction with humanistic care of emergency patients in China and its associated factors.From October 2023 to December 2023, a multi-center cross-sectional survey was conducted across 28 provinces and 87 hospitals in China, using a sampling method for inpatients in emergency department. Patient satisfaction with humanistic care was evaluated by a self-developed questionnaire with 32 items across 6 dimensions. Stepwise multiple linear regression was used to explore associated factors.total of 3003 valid questionnaires were successfully collected, with an effective rate of 86.05%. The emergency patients' total mean humanistic caring satisfaction score was 4.67±0.66. Age, medical insurance type, specialized emergency dept visited, waiting time, whether had accompanied person, hospital level, and hospital type are correlated factors (P＜0.05) regarding humanistic caring satisfaction. The correlation analysis showed perceived value and its three dimensions were moderately correlated with humanistic caring satisfaction. The multiple linear regression showed waiting time (β =-0.219, P＜ 0.05), whether had accompany person (β = -0.192, P＜0.05), hospital level (β = -0.137, P＜0.05), functional value (β =0.197, P＜0.05), emotional value (β =0.418, P＜0.05) were strong predictors.Hospitals at all levels should improve patients' perceived value, shorten waiting time, and provide caregivers with improved humanistic care in the emergency department.